The first UMP-EPT - Hafizoah, Kassim (Pusat Bahasa Moden dan Sains Kemanusiaan, 2012)
5 September 2012. UMP Strategic Plan 2011-2015 has set the standard of the students’ English language proficiency against the IELTS level. In order to achieve this target, the Modern Languages (ML) department of CMLHS suggested a few solutions which included the implementation of an English Proficiency Test (EPT).